2017
DOI: 10.3389/fpls.2017.00378
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of microRNAs in Agronomically Important Plants—Potential as Targets for Crop Improvement and Protection

Abstract: MicroRNAs (miRNAs) are a class of small non-coding RNAs that have recently emerged as important regulators of gene expression, mainly through cleavage and/or translation inhibition of the target mRNAs during or after transcription. miRNAs play important roles by regulating a multitude of biological processes in plants which include maintenance of genome integrity, development, metabolism, and adaptive responses toward environmental stresses. The increasing population of the world and their food demands require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(88 citation statements)
references
References 193 publications
1
87
0
Order By: Relevance
“…Transcription factors (TFs) and miRNAs are both considered as key regulators and have been well characterized in controlling the transcriptional events and ultimately the plant metabolic process (Djami‐Tchatchou et al ., ; Nigam et al ., ). TFs regulate gene expression by translating cis‐regulatory codes into specific gene‐regulatory events (Rothenberg, ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors (TFs) and miRNAs are both considered as key regulators and have been well characterized in controlling the transcriptional events and ultimately the plant metabolic process (Djami‐Tchatchou et al ., ; Nigam et al ., ). TFs regulate gene expression by translating cis‐regulatory codes into specific gene‐regulatory events (Rothenberg, ).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the function of HXK1 is dependent on the presence of brassinosteroids, which might act downstream of HXK1 to regulate hypocotyl elongation in A. thaliana in darkness (in a glucose-dependent reaction) [104]. Recent studies have indicated the involvement of several miRNAs in phytohormone signaling pathways [105] and in sugar responses in plants [106], but more research is needed to fill in some gaps in knowledge.…”
Section: Receiving and Transmitting The Signals Triggered By Sugarsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are approximately 20-25 nt long and are important post-transcriptional regulators that modulate gene expression by targeting mRNAs for translational repression or cleavage [10,11]. An increasing number of miRNAs have been identified and their sequences have been deposited in a publicly available database (http://www.mirbase.org/).…”
Section: Introductionmentioning
confidence: 99%